Rozproszone systemy ekspertowe - Sala, Dariusz; Cichoń, Dariusz (Distributed expert systems, 2006)
In this paper the authors show modern distributed expert systems, fields of their applications and the prospective areas of their development. They also analyze the internal structure of such systems as well as their tasks. The distributed expert systems are perceived as a next step in the development of inteligent computer applications which main aim is lo imitate the way an expert works and solves problems. The reason that explains why such systems exist and arc of high importance in the modern world is the process of globalization, and. in consequence, decentralization and dispersion of company’s units. Another important aspect of the distributed expert systems is the fact that thanks to their functions many users can make their decisions much easier. Such systems also enable them sharing sources of knowledge with each other.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 190-196